A Comparative Study Of The Three Point And Four Point Bending Behaviour Of Rigid Foam Core Glass/Epoxy Face Sheet Sandwich Composites. (2018) - Iyer, S. Vignesh; Chatterjee, Ritam; Ramya, M.; Suresh, E.; Padmanabhan, K.
Abstract: Sandwich composites are increasingly being used in the aerospace industry because of their bending stiffness-to-weight ratio. Floorboards, composite wing, horizontal stabilizer, composite rudder, landing gear door, speed brake, flap segments, aircraft interior and wingspans are typically made of sandwich composites. The investigation aims to carry out a comparative study between the three point and four point bending of rigid foam core glass epoxy skin sandwich composites. There arises a need to know whether the results rendered by four point bending are any different from three point bending, so the sandwich panels were fabricated using a hand lay-up process followed by vacuum bagging. Here, Polyurethane (PUF) and Polyisocyanurate (PIR) foams of density 125 kg/m 3 and 25mm thickness were used. Panels with skin to core weight ratios 3:1 and 4:1 were considered and a volume fraction of 0.3 was maintained for the face sheet. The samples were tested in accordance with the ASTM standards in three point and four point bending setups. Flexural properties like flexural rigidity, bending strength and normal stress are determined and compared for each of the cases. The three point bend setup is commonly used to study flexure in a structure while four point bend setup is preferred for longer spans and rigid structures. Flexural failures in either cases are observed, outlined and compared.